A Novel Silent Mutation in the L1CAM Gene Causing Fetal Hydrocephalus Detected by Whole-Exome Sequencing - Sun, Yixi; Li, Yanfeng; Chen, Min; Luo, Yuqin; Qian, Yeqing; Yang, Yanmei; Lu, Hong; Lou, Fenlan; Dong, Minyue (Frontiers in Genetics, 2019)
X-linked hydrocephalus (XLH), a genetic disorder, has an incidence of 1/30,000 male births. The great proportion of XLH is ascribed to loss of function mutations of L1 cell adhesion molecule gene (L1CAM), but silent mutations in L1CAM with pathogenic potential were rare, and were usually ignored especially in WES detection. In the present study, we describe a novel silent L1CAM mutation in a Chinese pregnant woman reporting continuous five times pregnancies with fetal hydrocephalus. After fetal blood sampling, we found c.453G>T (p.Gly151=) in L1CAM gene of the fetus by whole exome sequencing (WES), RT-PCR of the mRNA from cord blood mononuclear cells and subsequent sequence analysis identified the mutation created a potential 5' splice site consensus sequence, which would result in an in-frame deletion of 72 bp from exon 5 and 24 amino acids of the L1CAM protein. Heterozygous mutations were confirmed in analyzing DNA and mRNA from peripheral blood mononuclear cells of the woman, and, a severe L1 syndrome was confirmed by fetal ultrasound scan and MRI. Our study first indicated c.453G>T (p.Gly151=) in L1CAM could be disease causing for hydrocephalus, which would aid in genetic counseling for the prenatal diagnosis of hydrocephalus. Meanwhile, it suggested some silent mutations detected in WES should not be ignored, splicing predictions of these mutations were necessary.